DOI: 10.18130/v3fp54
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Journal Clubs on Intensive Care Nurses' Self-Report of Implementing Evidence into Practice

Abstract: Evidence-based practice (EBP) has been shown to reduce errors and improve patient outcomes with reductions in morbidity and mortality. Studies have also shown that not all nurses are using the latest evidence in their patient care. The barriers to the use of EBP include deficits in education, using outdated practices, and lack of discrediting of the outdated modes of practice. A quality improvement project was conducted to determine if journal clubs (JC) are a useful method of enhancing nurses' self-reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, since this study was self-reported by nurses, it is difficult to say that journal clubs actually have a real impact on promoting evidence-based nursing. Nonetheless, the effectiveness of this evidence-based teaching approach can be assessed through pre-test/post-test studies, which is suggested for future studies (Hill and Dillon, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, since this study was self-reported by nurses, it is difficult to say that journal clubs actually have a real impact on promoting evidence-based nursing. Nonetheless, the effectiveness of this evidence-based teaching approach can be assessed through pre-test/post-test studies, which is suggested for future studies (Hill and Dillon, 2016).…”
Section: Discussionmentioning
confidence: 99%